2018
DOI: 10.1002/jcb.27206
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: CRNDE promotes cell tongue squamous cell carcinoma cell growth and invasion through suppressing miR‐384

Abstract: Tongue squamous cell carcinoma (TSCC) is the most common type of oral cancer and is an aggressive head and neck malignancy. Increasing studies have demonstrated that long noncoding RNAs (lncRNAs) play important roles in diverse biological cell processes, such as cell development, fate decisions, cell differentiation, cell migration, and invasion. In our study, we showed that long noncoding RNA colorectal neoplasia differentially expressed (CRNDE) expression was upregulated in TSCC cell lines and tissues. Overe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 39 publications
(88 reference statements)
3
18
0
Order By: Relevance
“…20 Moreover, high CRNDE expression was demonstrated to promote cell proliferation, cell cycle and cell invasion in TSCC cell lines by negatively regulating miR-384. 8 In the present study, we veried that CRNDE was upregulated in TSCC tissues and cell lines, in accordance with previous result. 8 We also conformed that high CRNDE expression was associated with poor prognosis of TSCC patients.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…20 Moreover, high CRNDE expression was demonstrated to promote cell proliferation, cell cycle and cell invasion in TSCC cell lines by negatively regulating miR-384. 8 In the present study, we veried that CRNDE was upregulated in TSCC tissues and cell lines, in accordance with previous result. 8 We also conformed that high CRNDE expression was associated with poor prognosis of TSCC patients.…”
Section: Discussionsupporting
confidence: 92%
“…8 In the present study, we veried that CRNDE was upregulated in TSCC tissues and cell lines, in accordance with previous result. 8 We also conformed that high CRNDE expression was associated with poor prognosis of TSCC patients. Furthermore, we found that CRNDE knockdown repressed the proliferation, colony formation, migration and invasion while enhanced the apoptosis in TSCC cells in vitro, in accordance with former work.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Amounting reports have shown that lncRNAs could regulate cell proliferation, differentiation, stemness, survival, and epithelial–mesenchymal transition (Q. Xu et al, ; Yong et al, ; Zhu, Wang, Huang, et al, 2016). For instance, Ren et al () showed that lncRNA CRNDE is upregulated in tongue squamous cell carcinoma tissues and enhances tumor cell proliferation and metastasis via inhibiting miR‐384. L. Xu et al () reported that lncRNA LINC01296 overexpression predicts poor prognosis in patients with lung cancer and promotes tumor growth through regulating miR‐598/Twist1 pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive studies have suggested that lncRNAs could modulate survival, cell proliferation, stemness, differentiation, and epithelial-mesenchymal transition (EMT) [8][9][10]. For example, lncRNA CRNDE shows a high level in tongue squamous cell carcinoma tissues and inhibits miR-384 to facilitate cell proliferation and metastasis [11]. Besides, highlyexpressed LINC01296 is revealed to predict poor prognosis in lung cancer patients and enhances tumor growth via modulating miR-598/Twist1 pathway [12].…”
Section: Introductionmentioning
confidence: 99%